1993
DOI: 10.1161/01.str.24.4.539
|View full text |Cite
|
Sign up to set email alerts
|

Anterior ischemic optic neuropathy is not associated with carotid artery atherosclerosis.

Abstract: Background and Purpose: The relation between anterior ischemic optic neuropathy and carotid artery atherosclerotic disease is unclear. We studied patients with anterior ischemic optic neuropathy to determine if they had an increased occurrence of carotid artery stenosis.Methods: Fifteen consecutive patients with anterior ischemic optic neuropathy were evaluated prospectively for cervical carotid artery stenosis and compared with 30 age-and sex-matched asymptomatic patients and also with 11 age-and sex-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 28 publications
(12 reference statements)
2
22
0
Order By: Relevance
“…In a prospective study of nonsurgical patients, ION was not associated with carotid artery disease. 34 Although a basis for the notion that perioperative ION is related to atherosclerosis is that the optic nerve vasculature autoregulates abnormally, this association has not been studied in humans, and animal data are sparse and inconclusive. 43 Because of these unknowns, it appears advisable to approach patients undergoing highrisk procedures cautiously.…”
Section: Haemodilutionmentioning
confidence: 99%
“…In a prospective study of nonsurgical patients, ION was not associated with carotid artery disease. 34 Although a basis for the notion that perioperative ION is related to atherosclerosis is that the optic nerve vasculature autoregulates abnormally, this association has not been studied in humans, and animal data are sparse and inconclusive. 43 Because of these unknowns, it appears advisable to approach patients undergoing highrisk procedures cautiously.…”
Section: Haemodilutionmentioning
confidence: 99%
“…Smoking also does not appear to be an independent systemic risk factor [31], nor does carotid artery occlusion [32].…”
Section: Pathophysiologymentioning
confidence: 89%
“…In a prospective study of nonsurgical patients, ION was not associated with carotid artery disease. [22] However, Shapira et al [23] showed an association between prolonged epinephrine infusions or long bypass time and ION in patients undergoing open-heart surgery. One can possibly conclude that the presence of diabetes, intraoperative and postoperative low hematocrit and hypotension, need of epinephrine to support circulation independently need not necessarily cause POLV.…”
Section: Postoperative Vision Loss During Off-pump Coronary Artery Bymentioning
confidence: 99%